2018
DOI: 10.1123/jab.2017-0181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Posture Following a Single Session of Long-Duration Water Immersion

Abstract: Transitioning between different sensory environments is known to affect sensorimotor function and postural control. Water immersion presents a novel environmental stimulus common to many professional and recreational pursuits, but is not well-studied with regard to its sensorimotor effects upon transitioning back to land. The authors investigated the effects of long-duration water immersion on terrestrial postural control outcomes in veteran divers. Eleven healthy men completed a 6-hour thermoneutral pool dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Neutral buoyancy impacts other aspects of human perception and performance which may or may not match either Earth-normal behavior or behavior experienced in the environment found in other space analogs including human centrifugation 5 , microgravity aircraft flight 6 10 or long-duration bed rest 11 . For example, Glass et al 12 found that participants swayed less following long-duration water immersion compared to performance prior to exposure. They noted that proprioception 13 , somatosensation and vision 14 , possibly because human eyes evolved for viewing in air, are less informative of postural changes underwater and hypothesized that the sway changes may reflect a downweighting of these cues and a concomitant upweighting of vestibular input.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral buoyancy impacts other aspects of human perception and performance which may or may not match either Earth-normal behavior or behavior experienced in the environment found in other space analogs including human centrifugation 5 , microgravity aircraft flight 6 10 or long-duration bed rest 11 . For example, Glass et al 12 found that participants swayed less following long-duration water immersion compared to performance prior to exposure. They noted that proprioception 13 , somatosensation and vision 14 , possibly because human eyes evolved for viewing in air, are less informative of postural changes underwater and hypothesized that the sway changes may reflect a downweighting of these cues and a concomitant upweighting of vestibular input.…”
Section: Introductionmentioning
confidence: 99%
“…Neutral buoyancy may impact human perception and performance in a way that may or may not match either Earth-normal behaviour, behaviour in microgravity, or the behaviour found in space analogues such as human centrifugation 2 , microgravity aircraft flight 3 – 6 or long-duration bed rest 7 . Neutral buoyancy also introduces its own complications including distortions in visual perception due to light refraction at the glass-water interface between the participant’s goggles and the water column, and the effects of water pressure on the ears, an effect that is known to contribute to diver disorientation (see 8 and 9 for reviews). Does neutral buoyancy interfere with perceptual systems?…”
Section: Introductionmentioning
confidence: 99%
“…In space, both somatosensory and vestibular cues to the direction of gravity are compromised but in neutral buoyancy the vestibular cue remains unaffected while only the somatosensory cue, normally provided by pressure at the support surface, is disabled 10 , 11 , but see 8 for the potential of low-level connections between the vestibular and proprioceptive systems which argues for a low-level interaction between the two systems. Here we consider whether lack of the somatosensory cue affects the perception of self-orientation under neutral buoyancy conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation